1986
DOI: 10.1002/jcp.1041290212
|View full text |Cite
|
Sign up to set email alerts
|

Role of lipoproteins in growth of human adult arterial endothelial and smooth muscle cells in low lipoprotein‐deficient serum

Abstract: Recently improved culture conditions for human adult arterial endothelial and smooth muscle cells from a wide variety of donors have been used to study the effects of lipoproteins on proliferation of both cell types in low serum culture medium. Optimal growth of endothelial and smooth muscle cells in an optimal nutrient medium (MCDB 107) containing epidermal growth factor, a partially purified fraction from bovine brain, and 1% (v/v) lipoprotein-deficient serum was dependent on either high- or low-density lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…Normal endothelial cells (HUVEC) were isolated from human umbilical cord veins as described previously. 77 Cells were cultured in medium MCDB 107 (JRH Biosciences, Lenexa, KS, USA) supplemented with 2% FCS and a fibroblast growth factor-enriched fraction of porcine brain extract (1 mg/ml).…”
Section: Cell Linesmentioning
confidence: 99%
“…Normal endothelial cells (HUVEC) were isolated from human umbilical cord veins as described previously. 77 Cells were cultured in medium MCDB 107 (JRH Biosciences, Lenexa, KS, USA) supplemented with 2% FCS and a fibroblast growth factor-enriched fraction of porcine brain extract (1 mg/ml).…”
Section: Cell Linesmentioning
confidence: 99%
“…Whereas only a minimal effect was reported (Libby et al 1985), others found that LDL has a definite mitogenic effect (Fang et al, 1997;Locher et al, 1992). The effect was more pronounced when VSMC were cultured in low-serum medium (Chen et al, 1986) or when LDL was oxidized (Heery et al, 1995). In our system, LDL induced pronounced mitogenic activity that was further enhanced by extrinsic sPLA 2 .…”
Section: Lipoprotein Effect On Smooth Muscle Cellsmentioning
confidence: 47%
“…The impact of LDL on mitogenic activity of VSMC was found to vary, depending on experimental conditions (Chen et al, 1986;Fang et al, 1997;Heery et al, 1995;Leitinger et al, 1999;Libby et al, 1985;Locher et al, 1992;Scott-Burden et al, 1989). Whereas only a minimal effect was reported (Libby et al 1985), others found that LDL has a definite mitogenic effect (Fang et al, 1997;Locher et al, 1992).…”
Section: Lipoprotein Effect On Smooth Muscle Cellsmentioning
confidence: 99%
“…Lipoprotein-deficient serum (LPDS/was prepared from FBS by the method of Chen et al [15]. Briefly, FBS was adjusted to a density of 1.21 g/ml with solid potassium bromide (KBr) and centrifuged at 140,000 x g for 48 hours.…”
Section: Lipoprolein-d~fieient Serummentioning
confidence: 99%